2022
DOI: 10.3389/fpubh.2022.942243
|View full text |Cite
|
Sign up to set email alerts
|

Haze pollution reduction in Chinese cities: Has digital financial development played a role?

Abstract: Based on the exogenous shock of digital financial development in China in 2013, a difference-in-differences (DID) model is set up in this paper to investigate the causal relationship between digital financial development and haze pollution reduction. The finding of the paper is that a one standard deviation increase in digital finance after 2013 decreases the PM2.5 concentrations by 0.2708 standard deviations. After a number of robustness checks, like placebo tests, instrumental variable (IV) estimations, elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The digital economy has a negative impact on haze pollution, but the restraining effect is nonlinear and enhanced with the improvement of the development level of the digital economy. Technological innovation, industrial structure upgrading, and green development are the three main mechanisms for digital finance to reduce smog pollution [ 37 ]. Yang et al [ 38 ] explored the nonlinear mechanism of digital finance and haze pollution and found that a high level of economic development would help alleviate air pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The digital economy has a negative impact on haze pollution, but the restraining effect is nonlinear and enhanced with the improvement of the development level of the digital economy. Technological innovation, industrial structure upgrading, and green development are the three main mechanisms for digital finance to reduce smog pollution [ 37 ]. Yang et al [ 38 ] explored the nonlinear mechanism of digital finance and haze pollution and found that a high level of economic development would help alleviate air pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, in column (1) of Table 6 , we perform a placebo test by advancing the COVID-19 shock, which is widely used in robustness checks of DID estimations ( Chen and Zhao, 2022 ; Zhao and Yan, 2022 ). Specifically, we simulate the COVID-19 shock forward by one period, which is the 2017/2018 academic year based on our data feasibility.…”
Section: Resultsmentioning
confidence: 99%
“…The DID model is one of the classic methods to evaluate the effect of exogenous shocks, events, or policies, which is widely employed in social science (e.g., O’Connell et al, 2022 ; Zhao et al, 2022 ; Zhao and Yan, 2022 ). When evaluating the effects of a shock, such as the COVID-19 pandemic, if we just simply compare the difference of the dependent variable before and after the shock, the short-term trend changes may interfere with the estimation results and lead to the causality effects being uncertain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Digital finance has reduced the risk of commercial banks [34], eliminated the information monopoly of commercial banks, increased competition between commercial banks [35], and reduced the market power premium of the traditional banking sector, and therefore enables companies to access more favorable financial services. Furthermore, the growing use of technologies such as cloud computing, artificial intelligence, and blockchain has increased the efficiency of the operations and maintenance of financial institutions while decreasing the marginal cost of capital financing, i.e., the digital finance environment has reduced the cost of exogenous financing for enterprises [36]. (3) Digital finance increases investors' access to financial markets, broadens the investment channels for capital suppliers, and expands the supply of capital in the debt market [37].…”
Section: Digital Finance and Cash-holding Strategymentioning
confidence: 99%